The Politics of Translation in the Creation, Production, and Canon Formation of Translated Cebuano Literature from the Postwar Period to the Present - Estillore-Gabunada, Maria Vanessa (Archīum Ateneo, 2024)
The status of Cebuano literature in the Philippine literary field has been relegated to a marginalized position due to the outbreak of the Second World War and the implementation of English and Filipino as “Mediums of Instruction.” As a consequence, the development of Cebuano literature was thwarted. However, prominent Cebuano scholars exerted valuable effort to overcome the marginalized status of Cebuano literature through translation. Through translation, Cebuano literature started to be recognized in the Philippine literary field as translation projects of Cebuano literature were published and canonized. This study looks at the politics of translation and how it influences the production and canon formation of translated Cebuano literature. In doing so, this study traces the historical events from the 1970s to the 2010s to situate the narrative of the production process of Cebuano literature translation projects. Using the postcolonial translation theory of Andre Lefevere, this study identifies the constituencies that control the production process and investigates the agenda behind the production of Cebuano literature translation projects. Lastly, this study utilizes John Guillory’s theory of the canon, Barbara Herrnstein Smith’s contentions of “value/evaluation,” and Lawrence Venuti’s translation and canonization theory to elaborate how translation has influenced the formation of an alternative canon of Cebuano literature. Finally, this study draws its overall analysis on the material examination of Cebuano literature translation projects and on interviews with the constituencies (translators and publishers) to present the political issues in the production and canon formation of translated Cebuano literature.